Alternative tribological coatings to electrodeposited hard chromium: a critical review. (3rd July 2020) - Wang, S.; Ma, C.; Walsh, F. C.
ABSTRACT: The traditional importance of hard chromium electroplating in surface engineering is recognised and the key features of this well-established technology are summarised. Despite the high hardness, corrosion protection and wear resistance of chromium electrodeposits, a number of alternative coating compositions and application techniques have been developed for specific applications in tribology. Environmental challenges associated with hard chromium electroplating are highlighted and the need to develop and evaluate alternative coatings is stressed. Key examples of the alternative coatings are described, including their method of application, microstructure and tribological performance in controlled service environments. Research needs requiring rapid development are highlighted. A summary is given of the most competitive coatings and those having the potential to match the performance of hard chromium in selected applications are identified.